2016
DOI: 10.1016/j.ab.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

An assay for 26S proteasome activity based on fluorescence anisotropy measurements of dye-labeled protein substrates

Abstract: The 26S proteasome is the molecular machine at the center of the ubiquitin–proteasome system and is responsible for adjusting the concentrations of many cellular proteins. It is a drug target in several human diseases, and assays for the characterization of modulators of its activity are valuable. The 26S proteasome consists of two components: a core particle, which contains the proteolytic sites, and regulatory caps, which contain substrate receptors and substrate processing enzymes, including six ATPases. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
(92 reference statements)
0
22
0
Order By: Relevance
“…The CD was replaced either with domains 12–16 of human β-spectrin, which should function as a spacer of similar size to the CD [43] or with the central domain from Leu3, a related transcription factor [40, 44]. Although these hybrid proteins supported Gal1-mCherry expression, they blocked memory and were unresponsive to Gal1 (Figures 4C and D).…”
Section: Resultsmentioning
confidence: 99%
“…The CD was replaced either with domains 12–16 of human β-spectrin, which should function as a spacer of similar size to the CD [43] or with the central domain from Leu3, a related transcription factor [40, 44]. Although these hybrid proteins supported Gal1-mCherry expression, they blocked memory and were unresponsive to Gal1 (Figures 4C and D).…”
Section: Resultsmentioning
confidence: 99%
“…This titin-I27 V15P -35 substrate also contained a single lysine to enable the attachment of a poly-ubiquitin chain in a defined position. 10 The total time required for degradation of this substrate was determined by tracking the anisotropy of a fluorophore attached to the N-terminus of the titin folded domain (40). Gel-based assays confirmed the rapid degradation into peptides (Fig.…”
Section: Rapid Substrate Engagement Induces the Proteasome Conformatimentioning
confidence: 93%
“…The base sub-complex containing 4-azido-L-phenylalanine (AzF) was expressed, purified, and labeled using a similar procedure with the following modifications: In addition to pAM81, pMA83, and an amber-codon containing variant of pAM82, a fourth plasmid (pAM87) 40 containing the AzF tRNA synthetase/tRNA pair was used to co-transform Bl21 Star(DE3) E. coli. This plasmid was constructed by replacing the IPTG-inducible synthetase in the pULTRA-CNF construct designed by the Schultz lab with the AzFRS.2.t1 synthetase evolved by the Isaacs lab(34, 35).…”
Section: Purification and Labeling Of Unnatural Amino Acid-containingmentioning
confidence: 99%
“…By comparing the protein spots and their intensities under different conditions, the authors suggested that early sowing reduces antinutritional content among the genotypes irrespective of their growing conditions. Recently, fluorescent labeling of proteins has been used by researchers . Owing to the differential excitation and emission properties of the fluorescent‐labeled proteins, the identification of proteins is simplified and their quantification improved, which enhances experimental reproducibility.…”
Section: Protein Separationmentioning
confidence: 99%
“…Recently, fluorescent labeling of proteins has been used by researchers. 65,66 Owing to the differential excitation and emission properties of the fluorescent-labeled proteins, the identification of proteins is simplified and their quantification improved, which enhances experimental reproducibility. In another study, a three-dimensional (3D) approach which combines 2D HPLC/inductively coupled plasma mass spectrometry (ICP-MS) with SDS-PAGE was reported by Mataveli and Arruda 67 to study soybean metalloprotein information.…”
Section: Gel-based Separation/fractionation Of Proteinsmentioning
confidence: 99%